Figurações da memória nos romances The Remains of the Day e The Unconsoled, de Kazuo Ishiguro - Pereira, Tiago Ferreira (2021)
Although bridges between past and present are frequently established, it is clear that these connections prove, incrementally, to be incomplete, ambiguous and partial, since the practices of remembrance, in literary texts, emphasize given aesthetic-literary choices in the representation of memory. In this dissertation, based on indicated evidence, the objective was to study the creation of memory in the literature of Japanese-born British novelist Kazuo Ishiguro (1954) through the analysis of two of his novels, The Remains of the Day (1989) and The Unconsoled (1995). Kazuo Ishiguro is the author of eight novels and one short story collection, aside from other significant writings, and he was awarded the Nobel Prize in Literature (2017) for his body of work and the Man Booker Prize (1989) for The Remains of the Day. According to Shaffer (1998), Ishiguro is one of the most representative writers of a canon of contemporary English literature. Given the relevance of his work, the aim was not only to perform a critical examination of his literature supported by authors whose memory is discussed under social, philosophical, historical and literary views, such as Astrid Erll (2010), Ansgar Nünning (2010), Birgit Neumann (2010), Joël Candau (2011) and Maurice Halbwachs (2017), among others, but also to reflect on memory as processual construction and as product (representation). Among the aspects considered for analysis, we emphasize the following subthemes in their relationship with one another: 1) individual and collective memory; 2) memory and identity; and, finally, 3) memory, trauma and what is forgotten. Furthermore, the choice of the two works, The Remains of the Day and The Unconsoled, was made due to the fact that memory is represented as a plot thread and due to the evidence of its selectivity as mimetic process. Thus, memory, in Ishiguro’s works, is represented as reconstruction, as a constant updating of the past in specific social contexts, and subject to analysis of each of the previous subthemes such as individual and collective memory, identity, trauma and what is forgotten. To summarize, in these texts, Ishiguro shows that memory is not merely a series of impressions of the past, but a dynamic process, subject to social nuances, characterized by an ideological battle over the recording of these versions for future generations and having, as a basis, specific objectives regarding that.